2020
DOI: 10.3389/fmicb.2020.01037
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Suppresses the Parasitic Mite Vitellogenin by Antimicrobial Peptide

Abstract: The negative effects of honey bee parasitic mites and deformed wing virus (DWV) on honey bee and colony health have been well characterized. However, the relationship between DWV and mites, particularly viral replication inside the mites, remains unclear. Furthermore, the physiological outcomes of honey bee immune responses stimulated by DWV and the mite to the host (honey bee) and perhaps the pathogen/parasite (DWV/mite) are not yet understood. To answer these questions, we studied the tripartite interactions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The feeding activity of mites can increase pathogenicity of the virus through immunosuppression of bee host [52,56,57]. Recently, Wu et al described the tripartite interactions between honey bee pupae, T. mercedesae, and DWV and demonstrated that the expression levels of Defensin-1 and Hymenoptaecin are induced by DWV replication and T. mercedesae [58]. They found that the expression of hymenoptaecin in honeybee was negatively correlated with the mite vitellogenin (Vg) gene, which is essential for the reproduction of mite.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The feeding activity of mites can increase pathogenicity of the virus through immunosuppression of bee host [52,56,57]. Recently, Wu et al described the tripartite interactions between honey bee pupae, T. mercedesae, and DWV and demonstrated that the expression levels of Defensin-1 and Hymenoptaecin are induced by DWV replication and T. mercedesae [58]. They found that the expression of hymenoptaecin in honeybee was negatively correlated with the mite vitellogenin (Vg) gene, which is essential for the reproduction of mite.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…(524-750) antibody at the indicated amount of protein for min, and then added to the pupal head cells for infection as above. The dissected pupal head cells were pre-incubated with either purified VP1 P-domain protein (Wu et al, 2020) or BSA at the indicated amount of protein in the Grace culture medium for 1 h. DWV was then added for infection as above. Pre-incubation was conducted at room temperature.…”
Section: Infection Of Honey Bee Pupal Cells By Dwvmentioning
confidence: 99%
“…containing 5 % BSA for 1 h at room temperature followed by incubating with 1000-fold diluted anti-RdRP antibody (Wu et al, 2020) at 4 ℃ overnight. The membrane was washed three times with PBST (5 min each), and then incubated with 10,000-fold diluted IRDye® 680RD donkey anti-rabbit IgG (H+L) (LI-COR Biosciences) in PBST containing 5 % skim milk at room temperature for 1.5 h. The membrane was washed as above, and then visualized using Odyssey Imaging System (LI-COR Biosciences).…”
Section: Western Blotmentioning
confidence: 99%
“…The honey bee cuticle is perforated by mite’s chelicerae [ 13 ], and the hypostome is used to inject saliva and to suck host body fluids [ 14 , 15 ]. This ectophagous feeding habit has to mitigate or evade the immune reaction of the host in order to allow effective food uptake and use [ 16 ]. Moreover, mite feeding through an open wound exposes the host to the risk of infection by opportunistic pathogens [ 17 ].…”
Section: Introductionmentioning
confidence: 99%